2000
DOI: 10.1002/1096-987x(20010115)22:1<102::aid-jcc10>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of XPS and XES of diamond and graphite by DFT calculations using model molecules

Abstract: X-ray photoelectron and emission spectra (XPS and XES) of diamond and graphite have been analyzed by deMon density-functional theory (DFT) calculations using the model adamantane derivative (C 10 H 12 (CH 3 ) 4 ) and pyrene (C 16 H 10 ) molecules, respectively. The theoretical valence photoelectron and C Kα X-ray emission spectra for the allotrope are in good accordance with the experimental ones. The combined analysis of the valence XPS and C Kα XES enables us to divide the valence electronic distribution int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…Theoretical methods now accurately reproduce the elastic properties of diamond and provide robust predictions of their variations over the entire P-T range of Earth's interior (Nuñez Valdez et al 2012). The electronic properties of diamond are now well determined experimentally (Endo et al 2001), and there is excellent agreement with electronic structure calculations. On the other hand, the anharmonic properties of diamond are not fully understood .…”
Section: Stable Phasessupporting
confidence: 54%
“…Theoretical methods now accurately reproduce the elastic properties of diamond and provide robust predictions of their variations over the entire P-T range of Earth's interior (Nuñez Valdez et al 2012). The electronic properties of diamond are now well determined experimentally (Endo et al 2001), and there is excellent agreement with electronic structure calculations. On the other hand, the anharmonic properties of diamond are not fully understood .…”
Section: Stable Phasessupporting
confidence: 54%
“…Theoretical methods now accurately reproduce the elastic properties of diamond and provide robust predictions of their variations over the entire P-T range of Earth's interior (Nuñez Valdez et al 2012). The electronic properties of diamond are now well determined experimentally (Endo et al 2001), and there is excellent agreement with electronic structure calculations. On the other hand, the anharmonic properties of diamond are not fully understood (Gillet et al 1998).…”
Section: Stable Phasessupporting
confidence: 54%
“…337 The flat, broad peak at 15-20 eV is distinctly characteristic of graphite; whereas, sp 3 -hybridized carbon produces a sharp peak as first characterized by Shirley et al 338,339 and confirmed through DFT calculations. 340 Deconvolution of the C1s spectra is rigorous and will be explored in detail (vide infra).…”
mentioning
confidence: 99%